An Empirical Study of AI-enhanced Counselling Learning Theory to Develop LSRW Skills of Undergraduate Students (International Journal of Food and Nutritional Sciences, 2022)
This research explores the integration of Artificial Intelligence (AI) with Counseling Learning Theory (CLT) to enhance the LSRW skills (Listening, Speaking, Reading, and Writing) of ESL and EFL learners. AI tools, including speech recognition, chatbots, AI writing assistants, and adaptive listening platforms, complement the humanistic teaching approach by offering personalized feedback, real-time corrections, and anxiety-free practice environments. Thirty undergraduate engineering students participated in the study, divided into two groups. One group followed traditional CLT methods, while the other used AI-enhanced learning tools alongside CLT principles. Pre-tests and post-tests were conducted to assess improvements in students' communication skills. The results showed that the students using AI tools achieved better scores across all four skill areas compared to those in the traditional group. AI tools helped reduce communication anxiety, increased engagement, and provided individualized feedback, leading to faster and more effective learning outcomes. This study highlights the importance of combining humanistic approaches with technology, ensuring emotional security and continuous learning support. The findings suggest that AI integration can address common learning barriers, such as inhibition, insecurity, and limited practice opportunities. Future research can further explore the long-term impact of AI-driven solutions in different educational settings and develop best practices for implementing AI in language education.